A dictionary of Jewish-Christian relations - Kessler, Edward, 1963-; Wenborn, Neil (Cambridge University Press/Cambridge Centre for the Study of Jewish-Christian Relations, 2005)
Kessler and Wenborn's pioneering work explores and defines the many factors which characterise the relationship between Judaism and Christianity. It provides a comprehensive single reference to a subject which touches on numerous areas of study including theology, religious studies, history, Jewish studies, literature and social and political studies.